Molecular and cytogenetic study of east African highland banana - Nemecková, A.; Christelová, P.; Cížková, J.; Nyine, M.; Houwe, Ines van den; Svacina, R.; Uwimana, Brigitte; Swennen, Rony L.; Doležel, Jaroslav; Hribova, E. (Frontiers Media, 2018)
East African highland bananas (EAHBs) are staple food crop in Uganda, Tanzania, Burundi, and other countries in the African Great Lakes region. Even though several morphologically different types exist, all EAHBs are triploid and display minimal genetic variation. To provide more insights into the genetic variation within EAHBs, genotyping using simple sequence repeat (SSR) markers, molecular analysis of ITS1-5.8S-ITS2 region of ribosomal DNA locus, and the analysis of chromosomal distribution of ribosomal DNA sequences were done. A total of 38 triploid EAHB accessions available in the Musa germplasm collection (International Transit Centre, Leuven, Belgium) were characterized. Six diploid accessions of Musa acuminata ssp. zebrina, ssp. banksii, and ssp. malaccensis representing putative parents of EAHBs were included in the study. Flow cytometric estimation of 2C nuclear DNA content revealed small differences (max ~6.5%) in genome size among the EAHB clones. While no differences in the number of 45S and 5S rDNA loci were found, genotyping using 19 SSR markers resulted in grouping the EAHB accessions into four clusters. The DNA sequence analysis of the internal transcribed spacer region indicated a relation of EAHB clones with M. acuminata and, surprisingly, also with M. schizocarpa. The results suggest that EAHB cultivars originated from a single hybrid clone with M. acuminata ssp. zebrina and ssp. banksii being its most probable parents. Howeve